Analysis of Dielectric Barrier Discharge (DBD) Plasma System with Variation Flowrate to Increase Wettability Polytetrafluoroethylene (PTFE) - Aliffia Widyasari Putri Arbi; D.J. Djoko Herry Santjojo; Masruroh Masruroh (Kappa Journal, 2025)
Polytetrafluoroethylene (PTFE) is a widely used fluoropolymer with excellent thermal stability and chemical resistance. However, its hydrophobic nature makes it challenging to process and manage as waste. Plasma treatment is an effective method for modifying PTFE surface properties to improve wettability. This study investigates the effect of Dielectric Barrier Discharge (DBD) plasma treatment on PTFE with variations in oxygen gas flow rates. The plasma reactor was fabricated using a pyrex glass chamber, aluminum tape electrodes, and a stepper motor-driven stirring mechanism to ensure uniform exposure. PTFE samples were treated with DBD plasma at different oxygen flow rates (20–50 mL/min) for three minutes. Wettability changes were analyzed using Contact Angle Measurement (CAM), while plasma characterization was performed using Optical Emission Spectroscopy (OES). The results indicate that plasma treatment reduces the PTFE contact angle, improving its wettability. However, at higher flow rates, some samples adhered to the reactor walls, leading to uneven plasma exposure. The study concludes that plasma treatment effectively enhances PTFE wettability, but optimizing flow rate parameters is essential to ensure uniform surface modification.